Marketing Strategy Through Curriculum Innovation at SD Syahid Al-Khalifah Kendari (Strategi Marketing Melalui Inovasi Kurikulum di SD Syahid Al-Khalifah Kendari) - Nining Nining; Syahrul Syahrul; Erdiyanti Erdiyanti (Institut Agama Islam Negeri (IAIN) Kendari, 2022)
This article aims to analyze the practice of marketing strategies through curriculum innovation at SD Syahid Al-Khalifah Kendari. The aspects studied are: 1) the form of curriculum innovation offered by SD Syahid Al-Khalifah; 2) curriculum innovation as a marketing strategy at Syahid Al-Khalifah Elementary School. The research was conducted qualitatively with a narrative approach, so that field data were obtained from purposively selected informants, and the researcher acted as the main instrument, assisted by interview guides, camera-photos, and stationery. Data were collected using observation, interview, and document studies. To ensure the validity of this research data, the researchers carried out an extension of observations, increased persistence and triangulation. The results of this study indicate that curriculum innovation at SD Syahid Al-Khalifah Kendari is manifested in the integration of the 2013 curriculum, the Islamic curriculum, and the leadership curriculum. The node of the innovation is the formation of identity as a school of Islamic leadership. The curriculum innovation is a product that is sold to the public by using promotional media, both conventionally and using social media platforms.Keywords: Marketing Strategy, Curriculum Innovation, Islamic School, LeadershipArtikel ini bertujuan menganalisis praktik strategi marketing melalui inovasi kurikulum di SD Syahid Al-Khalifah Kendari. Aspek yang didalami adalah: 1) bentuk inovasi kurikulum yang ditawarkan SD Syahid Al-Khalifah; 2) inovasi kurikulum sebagai strategi marketing di SD Syahid Al-Khalifah. Penelitian dilakukan secara kualitatif dengan pendekatan naratif, sehingga data lapangan diperoleh dari informan yang dipilih secara purposive, dan peneliti bertindak sebagai instrumen utama, dibantu pedoman wawancara, kamera-foto, dan alat tulis. Data dikumpulkan dengan menggunakan teknik observasi, wawancara, dan studi dokumen. Untuk menjamin keabsahan data penelitian ini maka peneliti melakukan perpanjangan pengamatan, peningkatan ketekunan dan triangulasi. Hasil penelitian ini menunjukan bahwa inovasi kurikulum di SD Syahid Al-Khalifah Kendari mewujud dalam integrasi kurikulum 2013, kurikulum keislam, dan kurikulum kepemimpinan. Simpul dari inovasi tersebut adalah pembentukan identitas sebagai sekolah kepemimpinan Islam. Inovasi kurikulum tersebut menjadi produk yang dijual ke masyarakat dengan menggunak media promosi, baik secara konvensional maupun menggunakan platform media sosial.Kata Kunci: Strategi Marketing, Inovasi Kurikulum, Sekolah Islam, Kepemimpinan